The Role of Green Capital Women (GCW) in Green Business Digitalization (GBD) Through New Product Creation (NPC) in Ecoprint Business - Kartini, Tri Mulyani; Heriyanti, Sinta Sundari; Bimanti Esthi, Raniasari; Septiani, Rinda (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2024)
Women entrepreneurs in Yogyakarta and Solo in the ecoprint sector demonstrate a commitment to sustainability and play a significant role in the creative industry. They have great potential as agents of change for sustainable MSEs. The use of Green Knowledge (WGK) and Green Skills (WGS) is expected to accelerate Green Business Digitalization (GBD) through New Product Creation (NPC). This study aims to analyze the role of WGK and WGS on GBD through NPC. With a quantitative approach, this study involved women owners of ecoprint MSEs in Yogyakarta and Surakarta Residency, using a purposive sampling technique. The analysis used Structural Equation Modeling (SEM) and the Partial Least Square (PLS) approach. The results showed that WGK and WGS were significant to NPC but did not affect GBD through NPC; they directly affected GBD